Axial length and its associations in a Russian population: The Ural Eye and Medical Study - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Gilmanshin, Timur R.; Zainullin, Rinat M.; Arslangareeva, Inga I.; Salavatova, Venera F.; Bikbova, Guzel M.; Panda-Jonas, Songhomitra; Nikitin, Nikolai A.; Zaynetdinov, Artur F.; Nuriev, Ildar F.; Khikmatullin, Renat I.; et al. (PloS one, 2019)
To assess the normal distribution of axial length and its associations in a population of Russia. The population-based Ural Eye and Medical Study included 5,899 (80.5%) individuals out of 7328 eligible individuals aged 40+ years. The participants underwent an ocular and systemic examination. Axial length was measured sonographically (Ultra-compact A/B/P ultrasound system, Quantel Medical, Cournon d'Auvergne, France). Biometric data were available for 5707 (96.7%) individuals with a mean age of 58.8±10.6 years (range:40-94 years; 25%, 50%, 75% quartile: 51.0, 58.0, 66.0 years, respectively). Mean axial length was 23.30±1.10 mm (range: 19.02-32.87mm; 95% confidence interval (CI): 21.36-25.89; 25%, 50%, 75% quartile: 22.65mm, 23.23mm, 23.88mm, resp.). Prevalences of moderate myopia (axial length:24.5-<26.5mm) and high myopia (axial length >26.5mm) were 555/5707 (8.7%;95%CI:9.0,10.5) and 78/5707 (1.4%;95%CI:1.1,1.7), respectively. Longer axial length (mean:23.30±1.10mm) was associated (correlation coefficient r2:0.70) with older age (P<0.001;standardized regression coefficient beta:0.14), taller body height (P<0.001;beta:0.07), higher level of education (P<0.001;beta:0.04), higher intraocular pressure (P<0.001;beta:0.03), more myopic spherical refractive error (P<0.001;beta:-0.55), lower corneal refractive power (P<0.001;beta:-0.44), deeper anterior chamber depth (P<0.001;beta:0.20), wider anterior chamber angle (P<0.001;beta:0.05), thinner peripapillary retinal nerve fiber layer thickness (P<0.001;beta:-0.04), higher degree of macular fundus tessellation (P<0.001;beta:0.08), lower prevalence of epiretinal membranes (P = 0.01;beta-0.02) and pseudoexfoliation (P = 0.007;beta:-0.02) and higher prevalence of myopic maculopathy (P<0.001;beta:0.08). In that model, prevalence of age-related macular degeneration (any type: P = 0.84; early type: P = 0.46), diabetic retinopathy (P = 0.16), and region of habitation (P = 0.27) were not significantly associated with axial length. Mean axial length in this typically multi-ethnic Russian study population was comparable with values from populations in Singapore and Beijing. In contrast to previous studies, axial length was not significantly related with the prevalences of age-related macular degeneration and diabetic retinopathy or region of habitation.